Zmiany w obszarze ocen pracowniczych - Chomątowska, Barbara (The changes in the area of employees' appraisal, 2005)
This article shows the changes in the area of employees' appraisal- an important part of Human Resources Management. The changes are constantly taking place in the organization's inside and outside. This situation causes the difference in approach to evaluate of employees in the past and modem companies. This article shows the most important characteristics of modem approach to employees evaluations. In this way, we can see the progress in this area.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 542-547